Marginalizing Local Government in COVID-19 Containment: The Case of Kerala, India - Moolakkattu, John S. (Universitas Islam Indonesia, 2022)
Local governments (LGs) have an advantage in fighting pandemics compared to other levels of government. This is evident from the success stories of many local governments around the world. Because LGs are closer to the ground situation, they are able to act more contextually and flexibly. Pandemic containment measures like contact tracing, physical distancing, wearing of masks, quarantining, encouraging vaccination, and social support are easier for local governments to undertake with a certain degree of ownership. This paper analyses the role of rural LGs known as panchayats in containing pandemics, particularly Kerala, which has the most empowered village-level panchayats in India and has experience in participatory planning for more than two decades. The paper discusses Kerala's gains in pandemic management and the areas where it lagged.